Potenciali fotografij, posnetih s pametnim telefonom, za izmero prostovoljnih geografskih informacij - Triglav Čekada, Mihaela (Geografski vestnik, 2021)
The potential of smartphone images for measuring volunteered geographic information.This article presents the characteristics of smartphone images and their potential for collecting the volunteered geographic information. Today the smartphone image quality is equivalent to those taken with compact digital cameras, and they allow the real-time storage of the location from where the image was taken. Taking the example of processing a single image by using interactive orientation, these advantages are evaluatedin terms of their potential for photogrammetric measurements when updating topographic maps. Despitethe promising potential, the field of view extent of an image ultimately determines whether we will be ableto extract metric spatial 3D data from such an image.
Keywords: fotografije; fotogrametrija; geodezija; interactive orientation of images; kartografija; pametni telefoni; photogrammetry; smartphone images; topographic changes; volunteered geographic information